Hubungan Dukungan Sosial Dengan Keaktifan Berorganisasi Pada Lansia di Jemaat Gmim Bait-Lahim Talete 1 - Mandang, Jofie Hilda (Peneliti.net, 2023)
The activeness of elderly organizations is an interesting variable to study because it has a lot to do with the quality of life of the elderly. One of the variables that is theoretically constructive and in accordance with previous research is social support. This study aims to determine the relationship between social support and organizational activity in the elderly in the GMIM Bait-Lahim Talete One congregation. This study uses a correlational associative quantitative research method. Sampling using saturated sampling technique (census). Saturated sampling technique is a sampling technique when all members of the population are used as samples. Based on data on the population, the sample in this study was 40 elderly people, consisting of 25 women and 15 men. The results of the descriptive test stated that the social support received by the elderly was in the sufficient category and 92.5% of the elderly were active in organizations. After the normality and linearity assumptions were fulfilled, then a hypothesis test was carried out with the Pearson product moment correlation test with a significance of p: 0.000 < (α) 0.05 and the correlation coefficient was 0.715 which means there is a close relationship between social support and organizational activity in the elderly. The higher the social support, the higher the organizational activity of the elderly in the GMIM Bait-Lahim Talete One Congregation